2016
DOI: 10.1093/europace/euw100
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of ganglionic plexi ablation in a patient with neurally mediated syncope and intermittent atrioventricular block

Abstract: This is the first clinical case showing the differential effect of GP ablation on SA and AV nodal function, and critical importance of targeting the GP at the postero-inferior left atrium. The successful procedure corroborates clinical utility of ablation treatment instead of pacemaker implantation in selected patients with cardio-inhibitory NMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 20 publications
0
25
0
4
Order By: Relevance
“…Endocardial GP ablation has been increasingly used to treat severe vagal-related arrhythmias. [8][9][10][11][12][13][14] Although the guidelines 20 indicate pacemaker implantation for cases of symptomatic bradycardia and atrioventricular block, the fact that these patients are mostly young and otherwise healthy individuals encourages a more conservative approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endocardial GP ablation has been increasingly used to treat severe vagal-related arrhythmias. [8][9][10][11][12][13][14] Although the guidelines 20 indicate pacemaker implantation for cases of symptomatic bradycardia and atrioventricular block, the fact that these patients are mostly young and otherwise healthy individuals encourages a more conservative approach.…”
Section: Discussionmentioning
confidence: 99%
“…The diverse GP-mapping strategies used by different authors (1, high-frequency endocardial stimulation [2][3][4][5][6][8][9][10][11][12] ; 2, purely anatomic location 7,13 ; and 3, atrial electrogram characteristics 1,10,14,15 ) emerged as potential alternatives, with each one proposing specific end points (1, evoked reflex abolition; 2, ablation of all anatomic GP sites achieved; and 3, elimination of all fragmented potentials, respectively). However, some important questions still remain whichever technique is chosen:…”
Section: See Editorial By Mulpuru and Shenmentioning
confidence: 99%
See 1 more Smart Citation
“…The properties of the atrial wall and may be identified by changes in the spectrum as "AF Nests" [22][23][24][25] (this name resulted from its relation with the AF physiopathology as they present electrical resonance 26,27 favoring the AF maintenance).…”
Section: Rf Catheter Ablation For Vagal Denervationmentioning
confidence: 99%
“…). Essa mistura de células altera algumas propriedades elétricas da parede atrial e pode ser identificada por alterações no espectro como "ninhos de FA"[22][23][24][25] (esse nome é resultado da sua relação com a fisiopatologia da FA, pois apresentam ressonância elétrica26,27 . O terceiro neurônio está localizado no centro nervoso no núcleo dorsal do nervo vago, nos núcleos solitário e ambíguo.…”
unclassified